THE INFLUENCE OF PRICE, LOCATION, AND PRODUCT QUALITY ON PURCHASE DECISIONS (A STUDY ON HIDUP BARU FARM) - Fadhli Muharram; Fahri Haikal; R. Hario Sulistianto (Journal of Management and Leadership, 2026)
This study aims to determine: (1) the effect of price, (2) the effect of location, (3) the effect of product quality, and (4) the effect of price, location, and product quality on purchasing decisions at Hidup Baru Farm. The research method used was a quantitative method with a descriptive approach. The population in this study consisted of consumers of Hidup Baru Farm, with a sample of 75 respondents obtained using purposive sampling techniques. Data collection was carried out through questionnaires distributed using a Likert scale. The analytical method used was multiple linear regression with the assistance of SPSS version 32 software. The results showed that partially, price had no significant effect on purchasing decisions with a significance value of 0.161 > 0.05. Location also had no significant effect on purchasing decisions with a significance value of 0.689 > 0.05. Meanwhile, product quality had a positive and significant effect on purchasing decisions with a significance value of 0.017 < 0.05. Simultaneously, the results showed that price, location, and product quality had a positive and significant effect on purchasing decisions at Hidup Baru Farm.